2020
DOI: 10.3390/electronics9111791
|View full text |Cite
|
Sign up to set email alerts
|

First Principle Investigation of Electronic, Transport, and Bulk Properties of Zinc-Blende Magnesium Sulfide

Abstract: We have studied electronic, structural, and transport properties of zinc-blende magnesium sulfide (zb-MgS). We employed a local density approximation (LDA) potential and the linear combination of atomic orbitals (LCAO) method. Our computational method is able to reach the ground state of a material, as dictated by the second theorem of density functional theory (DFT). Consequently, our findings have the physical content of DFT and agree with available, corresponding experimental ones. The calculated band gap o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…We employed the Ceperley and Alder’s [ 20 ] local density approximation potential, which was parameterized by Vosko et al [ 21 ]. Based on DFT, it fully minimized the energy functional with the Bagayoko, Zhao, and Williams (BZW) method [ 22 , 23 , 24 ], as enhanced by Ekuma and Franklin (BZW-EF) [ 25 , 26 , 27 , 28 ], while implementing the linear combination of atomic orbitals (LCAO). We employed a program package developed at the Ames Laboratory of the U.S. Department of Energy, Ames, Iowa [ 29 , 30 ].…”
Section: Computational Methods and Related Detailsmentioning
confidence: 99%
“…We employed the Ceperley and Alder’s [ 20 ] local density approximation potential, which was parameterized by Vosko et al [ 21 ]. Based on DFT, it fully minimized the energy functional with the Bagayoko, Zhao, and Williams (BZW) method [ 22 , 23 , 24 ], as enhanced by Ekuma and Franklin (BZW-EF) [ 25 , 26 , 27 , 28 ], while implementing the linear combination of atomic orbitals (LCAO). We employed a program package developed at the Ames Laboratory of the U.S. Department of Energy, Ames, Iowa [ 29 , 30 ].…”
Section: Computational Methods and Related Detailsmentioning
confidence: 99%
“…It was observed that the MgS bandgap varied from 4.0 to 4.80 eV. [81][82][83][84][85]. Furthermore, it is observed that the absorbance shifts from 280 nm → 264 nm, as compared to the pure aqueous BSA solution, indicating three possibilities (i) formation of ultrasmall-sized nanocluster or (ii) electron transfer occurring between the tryptophan residue (BSA) and FMNCs, or (iii) both.…”
Section: Lifetime Analysismentioning
confidence: 98%